Type I IFN Signaling Is Dispensable during Secondary Viral Infection. - Martin P Hosking; Claudia T Flynn; J Lindsay Whitton (PLoS Pathogens)
Innate immune responses in general, and type I interferons (T1IFNs) in particular, play an important and often essential role during primary viral infections, by directly combatting the virus and by maximizing the primary adaptive immune response. Several studies have suggested that T1IFNs also contribute very substantially to the secondary (recall) response; they are thought (i) to be required to drive the early attrition of memory T cells, (ii) to support the subsequent expansion of surviving virus-specific memory cells, and (iii) to assist in the suppression and clearance of the infectious agent. However, many of these observations were predicated upon models in which T1IFN signaling was interrupted prior to a primary immune response, raising the possibility that the resulting memory cells might be intrinsically abnormal. We have directly addressed this by using an inducible-Cre model system in which the host remains genetically-intact during the primary response to infection, and in which T1IFN signaling can be effectively ablated prior to secondary viral challenge. We report that, in stark contrast to primary infection, T1IFN signaling is not required during the recall response. IFNαβR-deficient memory CD8+ and CD4+ memory T cells undergo attrition and expansion with kinetics that are indistinguishable from those of receptor-sufficient cells. Moreover, even in the absence of functional T1IFN signaling, the host's immune capacity to rapidly suppress, and then to eradicate, a secondary infection remains intact. Thus, this study shows that T1IFN signaling is dispensable during the recall response to a virus infection. Moreover, two broader implications may be drawn. First, a T cell's requirement for a cytokine is highly dependent on the cell's maturation / differentiation status. Consequently, second, these data underscore the importance of evaluating a gene's impact by modulating its expression or function in a temporally-controllable manner.